Bringing digital mental health to where it is needed most. (December 2017) - Ben-Zeev, Dror; Atkins, David
Mental health technologies, such as apps, clinical texting, social media platforms and web-based tools, have arrived. Channelling these resources to help people with serious mental illnesses, clinicians in need of support, and people in low-and middle-income countries will have the most impact on the global burden of mental illness.